Exploring global perspectives on the use of computer-based simulation in pharmacy education: a survey of students and educators - Gharib, Ahmed M.; Bindoff, Ivan K.; Peterson, Gregory M.; Salahudeen, Mohammed S. (Frontiers in Pharmacology, 2024)
Background: Increasing student numbers and logistical challenges in pharmacy education limit patient counselling and clinical placement opportunities. Computer-based simulation (CBS) offers scalable, interactive learning but faces integration barriers. Objective: To explore global perceptions of CBS implementation in pharmacy education among educators and students. Methods: An online cross-sectional survey was developed based on literature review and expert feedback. The survey was distributed globally through academic pharmacy organisations, social media, and the authors’ networks. It included 20 questions targeting pharmacy educators and students. Results: Responses from 152 educators across 38 countries and 392 students from 46 countries, spanning six WHO regions (AFRO, AMRO, EMRO, EURO, SEARO, and WPRO) were analysed using descriptive and inferential statistics. The majority of educators (90.1%, n=137) and students (84.2%, n=330) expressed comfort with using CBS and implementing it in their curriculum. Despite this, CBS was perceived as underutilised by 53.5% (n=81) of educators and 63.7% (n=250) of students. Students valued CBS for enhancing communication and problem-solving skills, while educators highlighted its relevance to community pharmacy practice. Both groups supported CBS use in assessments All educators (100%) identified workload reduction as a key priority, hoped CBS could assist in this area. Educators also reported barriers such as financial constraints (56.6%, n=86) and insufficient technical support (53.3%, n=81). On the other hand, students were less optimistic about institutional support, with only a few (7.4%, n=29) believed institutional leaders would actively support CBS adoption. Regional differences emerged, with SEARO (Southeast Asia) and AFRO (Africa) showing the lowest CBS usage rates. Educators in SEARO, AFRO, and EMRO (Eastern Mediterranean) raised concerns about technical support, while those in SEARO, AFRO, and WPRO (Western Pacific, including Australia, New Zealand, and Singapore) expressed financial concerns. Educators in AFRO and WPRO, however, reported being 100% comfortable with using CBS Conclusion: Both students and educators recognised the potential of CBS in pharmacy education, with strong support for its integration. Addressing barriers such as educator workload, financial constraints, and technical support is crucial for broader adoption. Improved resource allocation and targeted training for educators are essential to effectively incorporate CBS into the pharmacy curriculum.